A SYSTEM DYNAMIC MODEL OF THE TERRITORIAL DISTRIBUTED SERVICE SYSTEM - Beskorovainy, V.V.; Soboleva, E.V. (Radio Electronics, Computer Science, Control, 2013)
This paper reports the development of a System Dynamics model for the Strategic planning of a municipal service system. The model is capable of handling the critical variables that impact the operations of a delivery scheme. The model was developed using the Vensim programming software to handle the process dynamics. There are presented results of the proposed model simulation of the municipal service system with a 100 % increase of service demand. It is concluded that the model developed is sensitive to variable changes and has the capability of answering various operational what-if questions. As a strategic planning tool, the present model generates, for different scenarios, important operational information for the management of resources of the municipal service system.